USE OF DIFFERENT FUNGICIDES IN WHEAT UNDER WATER DEFICIT CONDITIONS - Bonfada, Bruno Mihlbeier; Carvalho, Ivan Ricardo; Loro, Murilo Vieira; Port, Eduarda Donadel; Pradebon, Leonardo Cesar (REVISTA DE AGRICULTURA, 2022)
The study aimed to evidence the efficiency of fungicides in disease control and the economic and productive effects under water deficit conditions in wheat. In addition, it sought to list the best management of fungicides so that the active principles can be more efficient in controlling diseases and, therefore, in the production of wheat grains. The experiment was carried out in São Borja – RS, in a randomized block design, with twenty treatments (fungicide management), in four replications, in 80 plots. The management composed by Versatilis + Versatilis potentiated the expression of cob length, number of grains per plant, leaf rust. Fusão + Fusão treatment promoted the lowest cob weight and grain weight per plant, similarly to Cypress + Mancozeb treatment. Orkestra + Fusão treatment enhanced grain yield and showed the best cost benefit, close to the value of the control treatment, proving to be the most profitable.